1994
DOI: 10.1097/00001888-199412000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric patients who select and those who refuse medical studentsʼ participation in their care

Abstract: Patients' needs for privacy, past experiences with student care, and expectations of student performance should be considered to ensure the respectful incorporation of student involvement in obstetric care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 0 publications
2
28
1
1
Order By: Relevance
“…Similar responses have been observed from patients in other clinical scenarios where more embarrassing examinations are necessary. 3,4 We found that blacks were less likely than whites to accept the presence of medical students and feel comfortable with teaching during the clinic visit. This result is consistent with Adams and colleagues 5 who reported that whites rated the benefit of the presence of a medical student higher than nonwhites.…”
Section: Discussionmentioning
confidence: 86%
“…Similar responses have been observed from patients in other clinical scenarios where more embarrassing examinations are necessary. 3,4 We found that blacks were less likely than whites to accept the presence of medical students and feel comfortable with teaching during the clinic visit. This result is consistent with Adams and colleagues 5 who reported that whites rated the benefit of the presence of a medical student higher than nonwhites.…”
Section: Discussionmentioning
confidence: 86%
“…While past positive experiences with medical students may increase comfort with medical student involvement in patient visits, the reverse has also been found. Magrane, Gannon, and Miller (1994) found that patients who refused medical student participation were more likely to hold negative views of their past medical student encounters. They found that 92% of women who recalled having previous experience with medical students and then subsequently refused medical student involvement classified those students as having "no effect" or a "negative effect" on the medical appointment or visit.…”
Section: Clinical Setting Variablesmentioning
confidence: 97%
“…Semelhantemente à literatura, esse achado mostrou que pacientes com boas experiên-cias prévias com estudantes têm maior disposição quanto ao envolvimento destes durante o atendimento 1,2,3,9,13 . Sob esta perspectiva, incentivar o primeiro contato da mulher com o acadêmico é recomendado, visto que experiências positivas minimizam o receio e reduzem a ansiedade que esse tipo de atendimento pode causar.…”
Section: Suzana Maria Pires Do Rio Et Al Prática Ginecológica: Visãounclassified